Association between dried fruit intake and pan-cancers incidence risk: A two-sample Mendelian randomization study - Jin, Chen; Li, Rui; Deng, Tuo; Lin, Zixia; Li, Haoqi; Yang, Yan; Su, Qing; Wang, Jingxian; Yang, Yi; Wang, Juejin; Chen, Gang; Wang, Yi (Frontiers in Nutrition, 2022)
Abstract Background Observational studies have revealed that dried fruit intake may be associated with cancer incidence, but the results are prone to be disturbed by confounding factors. Here, we conducted two-sample Mendelian randomization (MR) study to explore the causal relationship between dried fruit intake and eight site-specific cancers. Methods Forty-three single nucleoside polymers (SNPs) with robust genome-wide association study (GWAS) evidence, strongly correlated with dried fruit intake, were used as instrumental variables in this study. The summary-level genetic datasets of site-specific cancers were obtained from Oncoarray oral cavity and oropharyngeal cancer, International Lung Cancer Consortium, Breast Cancer Association Consortium, Ovarian Cancer Association Consortium, PanScan1, and GWAS of other scholars. We analyzed the causality between dried fruit intake and eight site-specific cancers using inverse-variance-weighted (IVW) and weighted median (WM) methods. In addition, for the results of MR analysis, Cochran's Q test was used to check the existence of heterogeneity, and multiplicative random effects were used to evaluate the heterogeneity further. Gene pleiotropy was tested by MR-Egger regression and MR-PRESSO methods. Results The evidence from IVW analyses showed that each increase of dried fruit intake by one standard deviation was statistically significantly associated with 82.68 % decrease of oral cavity/pharyngeal cancer incidence risk (P = 0.0131), 67.01 % decrease of lung cancer incidence risk (P = 0.0011), 77 % decrease of squamous cell lung cancer incidence risk (P = 0.0026), 53.07 % decrease of breast cancer incidence risk (P = 4.62 × 10 -5), 39.72 % decrease of ovarian cancer incidence risk (P = 0.0183), 97.26 % decrease of pancreatic cancer incidence risk (P = 0.0280); however, there was no significant effect on lung adenocarcinoma (P = 0.4343), endometrial cancer (P = 0.8495), thyroid cancer (P = 0.6352), and prostate cancer (P = 0.5354). The results of sensitivity analysis showed that our results are stable and reliable. Conclusions Intake of dried fruit may have a protective effect on some site-specific cancers. Therefore, health education and reasonable adjustment of dietary proportion may help realize the primary prevention of cancer.